I Segni del tempo. Il ritorno della consuetudine nell’era della complessità - Punzi, Antonio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The essay examines the role of custom today, moving away from the transformation of the relationship between law and time. The marginal role that modern rationalism attributed to custom was a consequence of the claim to control time by the predictive power of knowledge. The age of complexity, with its acceleration of time, paves the way for an unexpected return to custom, albeit in a new form.